Optimization of IoT-Based Sporting Goods Consumer Service Management System - Lihua Yu; Baobin Duan (Complexity)
With the rapid development of computer technology and information industry technology, the use of these technologies has been deeply applied to the management of various industries. Data time-sharing transmission can solve the problem that the system is not affected by the network; that is, it makes good use of the network and is not bound by the network. Even when the network speed is low or the network is not smooth, the system of each store can run normally, and when the network is smooth, the data will be uploaded in packets and automatically received by the server. The system is well designed with functional modules’ management, including sports goods import and export management, inventory management, membership management, and ledger management. System operation can well solve the coordination work between the head office and stores; the head office can master the operation of each store, check the generated ledger at any time, form statistical reports, and guide the operation status of each store so that the stores can adjust their operation methods and learn from each other at any time. The system network management can make valuable data information aggregated, rather than single data. The head office can make overall data backup promptly to provide good logistic support for each store.